Study of Frequency Modulated Boost Converter Operating in Discontinuous Conduction Mode - Stepins, D.; Jankovskis, J. (Elektronika ir Elektrotechnika, 2012)
In the paper output voltage ripples (OVR) of switching frequency modulated (FM) boost switch-mode power converter (SMPC) operating in discontinuous conduction mode (DCM) are examined thoroughly. Useful expressions to calculate OVR for closed-loop boost SMPC operating in DCM are derived and verified both using simulations in SIMULINK and experimentally. Influence of parameters of modulation and control signals on OVR is also examined. The results presented in the paper can be helpful when designing FM SMPC operating in DCM. Ill. 7, bibl. 12, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1819